2018
DOI: 10.3390/su10062039
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Value Discovery of Land Consolidation Projects: An Empirical Analysis of Shanghai, China

Abstract: The purpose of land consolidation is to promote moderately sized agricultural operations, intensive land use, concentrated population living and agglomerated industrial development. Previous research has primarily been macro-or mesoscale studies based on land ledger data, and analyzed only the effect of land consolidation on landscape ecological changes, only the resource and economic effects, or social effects or environmental effects of land consolidation. Aimed at addressing these shortcomings, an empirical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…In terms of ecological benefits, land remediation activities have positive impacts on optimizing natural ecosystems, functions, and environments [24][25][26] but may also bring risks and negative impacts on ecological environments [1,27]. Shi et al proposed that land remediation indirectly or directly improved the landscapeecological pattern of the project area [28]. Yang et al indicated that land remediation is an important measure to improve land-use efficiency and support land use.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of ecological benefits, land remediation activities have positive impacts on optimizing natural ecosystems, functions, and environments [24][25][26] but may also bring risks and negative impacts on ecological environments [1,27]. Shi et al proposed that land remediation indirectly or directly improved the landscapeecological pattern of the project area [28]. Yang et al indicated that land remediation is an important measure to improve land-use efficiency and support land use.…”
Section: Introductionmentioning
confidence: 99%
“…Although these units have less construction lands, they are mostly ecologically suitable zones, especially some scattered rural settlements and other construction lands such as mines and traffic facilities (Li and Fan 2014). As scattered construction lands have strong ecological disturbance, it is recommended to promote moderately concentrated land development, repair damaged landscape structures, and restore ecological functions by reducing scattered construction lands and ecologically restoring existing ones (Sun et al 2015;Shi et al 2018). As the ecological stress of construction lands are identified in this study based on EP simulation and related ecological zoning, the ecological restoration of construction lands as-identified here is important not only to protect ecological spaces but also to maintain potential EP and related functions (Li, Gao, and Chen 2019).…”
Section: Discussionmentioning
confidence: 99%
“…While enriching the structure and dis- of land consolidation includes three aspects: economic benefit, social benefit, and ecological benefit. Based on land-use patch data, Shi et al [55] combined landscape pattern analysis with production, life, and benefit evaluation to overcome the shortcomings of previous single-benefit evaluation and conduct comprehensive research on land consolidation projects. The results showed that land consolidation directly or indirectly improved the landscape ecological pattern of the project area, and land consolidation obviously improved the balanced distribution of cultivated land and the centralized distribution of construction land in the project area.…”
Section: Evolution Analysis Of Themes In the Field Of Land Consolidationmentioning
confidence: 99%